2018
DOI: 10.1111/jora.12464
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Communicative Openness on the Psychological Adjustment of Internationally Adopted Adolescents

Abstract: This study evaluated the predictive relationship between the communicative openness and psychological adjustment of adopted adolescents, controlling for preplacement risk factors. One hundred Spanish international adoptees aged 12-18 took part in the study. Data were gathered with a structured interview, the Youth Self Report and the Adoption Communication Scale. A history of maltreatment prior to the adoption was associated with more closed communication between parents and children. Prenatal drug exposure sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
(88 reference statements)
1
6
0
Order By: Relevance
“…Consistent with our expectations and with adoption literature (e.g., Aramburu Alegret et al, 2020;Brodzinsky, 2006;Colaner & Soliz, 2017;Ferrari et al, 2015b;Horstman et al, 2016), adolescents who feel free to discuss adoption-related issues with their parents appeared to be more prone to feeling that being adopted is important to who they are and report a higher score of satisfaction with their life. More speciically, our results showed an indirect effect of mother-child adoption communication openness on adoptees' present and future life satisfaction, through adoptive identity, and a direct effect of father-child adoption communication openness on adolescents' future life satisfaction.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with our expectations and with adoption literature (e.g., Aramburu Alegret et al, 2020;Brodzinsky, 2006;Colaner & Soliz, 2017;Ferrari et al, 2015b;Horstman et al, 2016), adolescents who feel free to discuss adoption-related issues with their parents appeared to be more prone to feeling that being adopted is important to who they are and report a higher score of satisfaction with their life. More speciically, our results showed an indirect effect of mother-child adoption communication openness on adoptees' present and future life satisfaction, through adoptive identity, and a direct effect of father-child adoption communication openness on adolescents' future life satisfaction.…”
Section: Discussionsupporting
confidence: 89%
“…Using the resilience paradigm, recent studies evidenced that a positive parent-child relationship protects children against risk factors, not only during the irst post-adoption stages, but also during adolescence and throughout the transition to adulthood (e.g., Ferrari et al, 2015b;Koh & Rueter, 2011;Lee, 2016;Palacios & Brodzinsky, 2010;Ranieri et al, 2017;Tarroja, 2015). Speciically, there is substantial evidence to suggest that communication in general, and especially in terms of openness on adoption-related issues, plays a pivotal role within adoptive families (Aramburu Alegret et al, 2020;Lanz et al, 1999;Rueter & Koerner, 2008).…”
Section: Adoption Communication Openness and Adoptees' Adjustmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Communication openness. The impact of communication openness where the adoptive parents recognise rather than deny the inherent differences associated with being an adoptive family was explored in six studies (Aramburu Alegret, et al, 2020;Brodzinsky, 2006;Grotevant, et al, 2011;Le Mare and Audet, 2014;Soares, et al, 2017;Tarroja) and was found to be a generally positive association.…”
Section: Family Factorsmentioning
confidence: 99%
“…To the best of our knowledge, there is a paucity of studies that analyze when adoptive families start to communicate about adoption-related issues. Choosing when to begin to communicate may be difficult for adoptive parents, so they often seek support through post-adoption services [16]. Indeed, for adoptive parents, talking about the child's past life means sharing information about the life-changing and traumatic events that the child has experienced (i.e., abandonment, loss of their birth family, departure from their birth country in the case of international adoption).…”
Section: Introductionmentioning
confidence: 99%